Time-synchronous-averaging of gear-meshing-vibration transducer responses for elimination of harmonic contributions from the mating gear and the gear pair. (October 2015) - Mark, William D.
Abstract: The transmission-error frequency spectrum of meshing gear pairs, operating at constant speed and constant loading, is decomposed into harmonics arising from the fundamental period of the gear pair, rotational harmonics of the individual gears of the pair, and tooth-meshing harmonics. In the case of hunting-tooth gear pairs, no rotational harmonics from the individual gears, other than the tooth-meshing harmonics, are shown to occur at the same frequencies. Time-synchronous averages utilizing a number of contiguous revolutions of the gear of interest equal to an integer multiple of the number of teeth on the mating gear is shown to eliminate non-tooth-meshing transmission-error rotational-harmonic contributions from the mating gear, and those from the gear pair, in the case of hunting-tooth gear pairs, and to minimize these contributions in the case of non-hunting-tooth gear pairs. An example computation is shown to illustrate the effectiveness of the suggested time-synchronous-averaging procedure. Highlights: Describes harmonic contributions of meshing gear-pairs. Describes synchronous averaging to isolate contributions from each gear of meshing pair. Separates rotational harmonics from each gear of meshing pair. Illustrates gear-health-monitoring properties of hunting-tooth gears.